Impact of Primary Diagnosis on the Outcome of Heart Transplantation in Children - Csaba Vilmányi; Zsolt L. Nagy; György S. Reusz; László Ablonczy (Journal of Cardiovascular Development and Disease)
Introduction: Pediatric heart transplantation (HTX) remains the only therapeutic option for end-stage heart failure not amenable to conventional surgical or catheter interventions. We reviewed our pediatric HTX outcomes according to primary diagnosis. Patients and Methods: Sixty-two patients underwent HTX between 01/2007 and 12/2022. Patients were divided into congenital heart disease (CHD, n = 20) and cardiomyopathy (CMP, n = 42) groups. All potential variables relevant to patient recovery and long-term survival with endpoints of retransplantation or death were analyzed. Results: CHD patients underwent HTX after significantly more multiple major cardiac surgeries per patient (2.5 [0–5]) than CMP patients (0.5 [0–2], p < 0.01), without notable allosensitization. Post-HTX recovery was longer in CHD (mean mechanical ventilation 7 vs. 3 days, p = 0.001), likely due to longer surgical time (468 vs. 375 min, p = 0.037). There were no significant differences in the frequency of rejections between the two groups (4/20 vs. 9/42). Midterm survival was slightly better (85/70% p = NS) in CMP (median follow-up 44.5 [0–177] months). Conclusion: Our study confirmed good short- and long-term outcomes of pediatric HTX in both CMP and CHD. The longer postoperative recovery in CHD did not lead to higher mortality. No higher pretransplant hypersensitization was observed, possibly explaining the lack of difference in the number and severity of rejections.